Respuesta :

7n2-7 = 7 (n -1)(n+1)

Answer: 7(n + 1)(n - 1)

Step-by-step explanation:

[tex]7n^2-7[/tex]

[tex]\mathrm{Rewrite\:}7\mathrm{\:as\:}7\cdot \:1[/tex]

[tex]=7n^2-7\cdot \:1[/tex]

[tex]$ Factor out the common term 7[/tex]

[tex]=7\left(n^2-1\right)[/tex]

[tex]$ Factor $n^2 - 1[/tex]

[tex]\mathrm{Rewrite\:}1\mathrm{\:as\:}1^2[/tex]

[tex]=n^2-1^2[/tex]

[tex]$ Apply difference of two squares formula $ x^2 - y^2 = (x+y)(x-y)[/tex]

[tex]n^2-1^2=\left(n+1\right)\left(n-1\right)[/tex]

[tex]\therefore \bf{7\left(n+1\right)\left(n-1\right)}[/tex]